BRAIN NATRIURETIC PEPTIDE AS BIOCHEMICAL MARKER FOR STRUCTURAL AND FUNCTIONAL HEART DISORDERS IN ARTERIAL HYPERTENSION - S. V. Ivanova; Yu. A. Vasyuk; E. Yu. Shupenina; P. V. Krikunov; I. A. Sadulaeva (Российский кардиологический журнал)
Aim. Assessment of structural and functional condition of the left and right heart chambers related to the level of NT-proBNP and clinical signs of CHD in AH patients.Material and methods. Totally, 137 AH patients studied (45 men, 92 women) with sinus rhythm and EF LV ≥50%. All patients underwent standard investigations, 6-minute walking test, two-dimension EchoCG, transvalvular and tissue Dopplergraphy, treadmill-test, NT-proBNP concentration in plasma. Assessment of structural and functional heart condition was done in three defined groups according to NT-proBNP level (norm, “grey” zone, elevated NT-proBNP).Results. The level of NT-proBNP is related to the age, sex, therapy intake regularity and does not relate to body mass, BP level, heart rate. The relation revealed for NTproBNP level and diastolic dysfunction of the LV by the data of transmitral and tissue Doppler-graphy. Modified Tei index, obtained during impulse-wave tissue Dopplergraphy, was the most informative marker of LV dysfunction, relevant of NT-proBNP levels. The increase of NT-proBNP followed by significant increase of RV wall thickness. Evaluation of NT-proBNP together with EchoCG led to revelation of asympthomatic LV dysfunction in 13,1% of patients.Conclusion. Interpretation of NT-proBNP level in hypertensive must complex, taking into consideration clinical factors as risk factors, gender and age. Evaluation of NT-proBNP with echocardiography helps to identify groups of patients of higher cardiovascular risk and to optimize further treatment.